Tectono-stratigraphic evolution of the Permo-Triassic succession in the fars platform of Iran: Implications for future exploration of the Paleozoic petroleum system. (November 2021) - Alipour, Majid; Alizadeh, Bahram; Mirzaie, Shohreh
Graphical abstract: Highlights: Salt tectonics has influenced the Paleozoic petroleum system of the Fars Platform. Withdrawal synclines control the thickness/facies of the Permo-Triassic sequences. Considerable potential exists for stratigraphic traps in this petroleum system. Abstract: Using a new tectono-stratigraphic framework, this paper investigates the Paleozoic petroleum system of the Fars Platform (Southwest Iran). The essential elements and processes of this prolific petroleum system were strongly impacted during both syn -rift and post-rift phases. Extensive erosion during the syn -rift phase led to the local removal of the Latest Ordovician-Earliest Silurian Sarchahan source rock and deposition of continental clastic sediments which acted as important carrier rocks during hydrocarbon migration. During the post-rift phase, syn -depositional salt tectonics predominantly controlled the stratigraphy of the Permo-Triassic strata. The salt- withdrawal synclines not only controlled the facies and thickness of the reservoir-seal couplets, but also promoted hydrocarbon generation from the Silurian source rock in the resulting depocenters. These hydrocarbons could migrate toward structurally higher areas through areally-continuous carriers of the Lower Permian Faraghan Formation and from huge accumulations below efficient evaporitic seals. This model can better explain the present-day distribution of Paleozoic accumulations in the Fars Platform and sheds new light on the remaining potential (in stratigraphic traps) within the Paleozoic petroleum system.